Claras intrusion a slab break-off model for mafic–ultramafic igneous rocks in the south Brasília Belt: insights related to post-collisional magmatism - Carvalho, D.R.D.; Aguiar, I.M.; Temporim, F.A.; Melo, R.P. [UNESP]; Yokoyama, E.; Carneiro, J.S.M; Santiago, R.M. (Elsevier, 2025)
The extensional phase of orogens records the evolution of the lithospheric mantle along convergent plate boundaries, spanning from pre- to post-collisional stages. Post-collisional mafic-ultramafic magmatism may represent the ascent of asthenospheric magmas during orogenic collapse and the contribution of metasomatized lithospheric sources in the final stages of orogenesis. The Águas Claras intrusion (AC), situated within the Arenópolis Magmatic Arc in the southern segment of the Brasília Belt (BB), constitutes part of a suite of Ediacaran post-collisional mafic-ultramafic intrusions. We present a detailed analysis of the AC intrusive body based on geological and the integration of new and available geochemical data. The lithotypes of the AC are petrographically identified as peridotites, pyroxenites, and norites. The samples are part of the tholeiitic series, with Mg enrichment. The magma that generated the analyzed rocks has heterogeneous mantle sources. The AC rocks have a mantle source related to the asthenosphere with little interaction with the lithospheric mantle. Through the results of this work the adiabatic decompression melting of the asthenosphere necessary for magmatism may have been triggered by some major tectonic disturbance of the subducted plate. Therefore, a slab break-off model is proposed for BB. This is in agreement with a review of BB that suggested a model in which in the period between approximately 660 and 620 Ma the evolution of the Arenópolis Arc was the result of alternating extension events associated with short episodes of plate tilting. These findings provide significant insights into the post-collisional tectonic evolution of the BB, supporting a slab break-off model as the principal mechanism for the generation of mafic-ultramafic magmatism during late Ediacaran times.